Purification and characterization of xylanases from Trichoderma inhamatum - Silva, L. A. O.; Fanchini Terrasan, Cesar Rafael [UNESP]; Carmona, Eleonora Cano [UNESP] (Univ Catolica De Valparaiso, 2015)
Background: Two xylanases, Xyl I and Xyl II, were purified from the crude extracellular extract of a Trichoderma inhamatum strain cultivated in liquid medium with oat spelts xylan. Results: The molecular masses of the purified enzymes estimated by SDS-PAGE and gel filtration were, respectively, 19 and 14 kDa for Xyl I and 21 and 14.6 kDa for Xyl II. The enzymes are glycoproteins with optimum activity at 50 degrees C in pH 5.0-5.5 for Xyl I and 5.5 for Xyl II. The xylanases were very stable at 40 degrees C and in the pH ranges from 4.5-6.5 for Xyl I and 4.0-8.0 for Xyl II. The ion Hg2+ and the detergent SDS strongly reduced the activity while 1,4-dithiothreitol stimulated both enzymes. The xylanases showed specificity for xylan, K-m and V-max of 14.5, 1.6 mg.mL(-1) and 2680.2 and 462.2 U.mg of protein(-1) (Xyl I) and 10.7, 4.0 mg.mL(-1) and 4553.7 and 1972.7 U.mg of protein-1 (Xyl II) on oat spelts and birchwood xylan, respectively. The hydrolysis of oat spelts xylan released xylobiose, xylotriose, xylotetrose and larger xylooligosaccharides. Conclusions: The enzymes present potential for application in industrial processes that require activity in acid conditions, wide-ranging pH stability, such as for animal feed, or juice and wine industries. (C) 2015 Pontificia Universidad Catolica de Valparaiso. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Enzyme purification; Physico-chemical properties; Trichoderma inhamatum; Xylanases